Reversible Right-Sided Heart Failure Secondary to Carcinoid Crisis - Mariana Soto Herrera; José A. Restrepo; Jesús H. Díaz; Andrés Ramos; Andrés Felipe Buitrago; Mabel Gómez Mejía (Case Reports in Critical Care)
Carcinoid crisis is an infrequent and little-described complication of neuroendocrine tumors that can be life threatening. It may develop during induction of anesthesia, intraoperatively, during tumor manipulation and arterial embolization, or even spontaneously. The massive release of neuroendocrine substances can lead to potentially fatal complications. Somatostatin analogs inhibit the release of these substances and are the mainstay of treatment. The following case report describes a patient with reversible acute right-sided heart failure posterior to hepatic artery embolization.